SUMO1 SUMOylates and SENP3 deSUMOylates NLRP3 to orchestrate the inflammasome activation. Issue 1 (2nd December 2019) - Shao, Luyao; Liu, Yan; Wang, Wenbiao; Li, Aixin; Wan, Pin; Liu, Weiyong; Shereen, Muhammad Adnan; Liu, Fang; Zhang, Wen; Tan, Quiping; Wu, Kailang; Liu, Yingle; et al.
Abstract: The NLRP3 inflammasome regulates innate immune and inflammatory responses by promoting caspase1‐dependent induction of pro‐inflammatory cytokines. However, aberrant inflammasome activation causes diverse diseases, and thus inflammasome activity must be tightly controlled. Here, we reveal a molecular mechanism underlying the regulation of NLRP3 inflammasome. NLRP3 interacts with SUMO‐conjugating enzyme (UBC9), which subsequently promotes small ubiquitin‐like modifier 1 (SUMO1) to catalyze NLRP3 SUMOylation at residue Lys 204 . SUMO1‐catalyzed SUMOylation of NLRP3 facilitates ASC oligomerization, inflammasome activation, and interleukin‐1β secretion. Moreover, this study also reveals that SUMO‐specific protease 3 (SENP3) is required for the deSUMOylation of NLRP3. Interestingly, SENP3 deSUMOylates NLRP3 to attenuate ASC recruitment and speck formation, the NLRP3 inflammasome activation, as well as IL‐1β cleavage and secretion. In conclusion, we reveal that SUMO1‐catalyzed SUMOylation and SENP3‐mediated deSUMOylation of NLRP3 orchestrate the inflammasome activation.